Preliminary phytochemical profile of Dictyota dichotoma (Huds.) Lamouroux collected from Koothankuzhi Coast, Tirunelveli district, Tamil Nadu, India - John Peter, Paul J (Journal of Drug Delivery and Therapeutics, 2018)
The present study was intended to discover the preliminary phytochemicals of Dictyota dichotoma (Huds.) Lamouroux from Koothankuzhi coast, Tirunelveli district, the south east coast of Tamil Nadu, India. The preliminary phytochemical analysis was conducted in seven extracts namely methanol, acetone, chloroform, ethyl acetate, petroleum ether, hexane and benzene by Harborne method. The preliminary phytochemical analysis showed the presence of alkaloids, anthocyanin, anthraquinones, cardiac glycosides, catechin, coumarins, diterpenes, emodins, flavonoids, glycosides, leucoanthocyanin, lignins, phenols, phlobatannins, quinones, saponins, steroids, tannins, terpenoids and triterpenoids. Among the various phytochemicals studied, tannin showed the maximum presence, being found in seven different extracts and anthraquinones was observed in only one extract. From the results, it was noted that the extracts of Dictyota dichotoma (Huds.) Lamouroux was found to be the presence of a number of active secondary metabolites. This report will lead to the isolation and characterization of these active secondary metabolites for bioefficacy and bioactivity.Keywords: Phytochemical, Bioactive compounds, Seaweed extracts, Dictyota, Tamil Nadu.